1994
DOI: 10.1161/01.cir.89.2.667
|View full text |Cite
|
Sign up to set email alerts
|

Regional myocardial sympathetic dysinnervation in arrhythmogenic right ventricular cardiomyopathy. An analysis using 123I-meta-iodobenzylguanidine scintigraphy.

Abstract: In patients with ARVC, regional abnormalities of sympathetic innervation are frequent and can be demonstrated by 123I-MIBG scintigraphy. Sympathetic denervation appears to be the underlying mechanism of reduced 123I-MIBG uptake and may be related to frequent provocation of ventricular arrhythmias by exercise or catecholamine exposure in ARVC. Therefore, in patients with ARVC, the noninvasive detection of localized sympathetic denervation by 123I-MIBG imaging may have implications for the early diagnosis and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
2
6

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(112 citation statements)
references
References 70 publications
6
96
2
6
Order By: Relevance
“…[1][2][3] Because sympathetic nerve fibers travel in the subepicardium, localized presynaptic sympathetic denervation may occur early in the course of the disease process before functional abnormalities become apparent. 2,7 However, the findings of the present study do not support the presence of such a denervation process underlying sympathetic dysinnervation in ARVC. Analysis of the tracer clearance rate from the myocardium revealed substantially higher blood flow-corrected k 2 values (ie, k 2 /MBF) for the 4 subjects who had a reduced V d for 11 C-HED (subjects 1, 4, 6, and 7), whereas this parameter was normal for the 4 subjects with normal or high values of V d .…”
Section: Denervationcontrasting
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] Because sympathetic nerve fibers travel in the subepicardium, localized presynaptic sympathetic denervation may occur early in the course of the disease process before functional abnormalities become apparent. 2,7 However, the findings of the present study do not support the presence of such a denervation process underlying sympathetic dysinnervation in ARVC. Analysis of the tracer clearance rate from the myocardium revealed substantially higher blood flow-corrected k 2 values (ie, k 2 /MBF) for the 4 subjects who had a reduced V d for 11 C-HED (subjects 1, 4, 6, and 7), whereas this parameter was normal for the 4 subjects with normal or high values of V d .…”
Section: Denervationcontrasting
confidence: 99%
“…Regional abnormalities of presynaptic adrenergic function were not as extensive as previously reported in studies using 123 I-MIBG SPECT 7 and were found in only 4 patients with ARVC in the present study. This may be explained by patient selection, which was not based on the results of preceding 123 I-MIBG scanning but rather on the absence of previous treatment with antiadrenergic drugs.…”
Section: Study Limitationssupporting
confidence: 67%
See 2 more Smart Citations
“…[1][2][3][4][5][6] Although the importance of the autonomic nervous system in atrial fibrillation (AF) has been suggested by both experimental and clinical observations, its role in the initiation and perpetuation of AF has not been determined. The autonomic tone before the onset of AF has been used to identify so-called vagal AF in humans.…”
mentioning
confidence: 99%